PECULIARITIES OF VARIOUS TYPES OF CIVIC IDENTITY - Petrovska, Inha (Journal of Education Culture and Society, 2019)
Aim. The aim of the research is to determine the psychological peculiarities of citizens with various types of civic identity. Methods. 190 Ukrainian citizens were interviewed about their relations with parents (or guardians) in the childhood , features of family upbringing, priority values of the parents’ family, experience of interpersonal relationships with peers, participation in school/student activities, lifestyle, etc. The following psycho-diagnostic techniques were also used: questionnaire "Level and Type of Civic Identity" (Petrovska, 2018); "World Assumptions Scale" (Janoff-Bulman, adapted by Padun & Kotelnikova, 2008); "Portrait Values Questionnaire" (Schwartz, adapted by Semkiv, 2013); "Interpersonal Trust Scale" (Rotter, adapted by Dostovalov, 2000); questionnaire "Level of Social Frustration" (Vasserman, 2004); "Social Activity Scale" (Lewicka, adapted by Cholij, 2010). Results. The typology of citizens ("devoted", "moderate", "disappointed", "indifferent" and "alienated") was created in accordance with the specificity of the formation of civic identity components (cognitive, value, affective, behavioral). Significance (value)/insignificance, positive/negative attitude towards belonging to the state and community of citizens and forms of activity/inactivity in relation to the state and citizens made up the basis of the classification. Also, psychological peculiarities of citizens with foregoing types of civic identity were determined. Conclusions. The main factors in the formation of a certain type of civic identity are basic beliefs (in particular, the justice of the world, the ability to control the events of one’s life and self-value); civic behavioral patterns of reference persons (including civic attitudes of reference persons); social integration and social acceptance (experience of interpersonal relationships with peers); subjectness activity (defending own position, wide range of interests, initiative, active participation in many events); value-semantic orientations (in particular, universalism, self-regulation, safety, tradition); prosocial focus (focus of activity on socially useful affairs); social trust; the fact of meeting the needs of physical and social existence in the state (level of social frustration); experience of interaction with the state in the form of its various agencies.